Improving the culture of interdisciplinary collaboration in ecology by expanding measures of success - Goring, Simon J.; Weathers, Kathleen C.; Dodds, Walter K.; Soranno, Patricia A.; Sweet, Lynn C.; Cheruvelil, Kendra S.; Kominoski, John S.; Rüegg, Janine; Thorn, Alexandra M.; Utz, Ryan M. (My University, 2014)
Interdisciplinary collaboration is essential to understand ecological systems at scales critical to human decision making. Current reward structures are problematic for scientists engaged in interdisciplinary research, particularly early career researchers, because academic culture tends to value only some research outputs, such as primary-authored publications. Here, we present a framework for the costs and benefits of collaboration, with a focus on early career stages, and show how the implementation of novel measures of success can help defray the costs of collaboration. Success measures at team and individual levels include research outputs other than publications, including educational outcomes, dataset creation, outreach products (eg blogs or social media), and the application of scientific results to policy or management activities. Promotion and adoption of new measures of success will require concerted effort by both collaborators and their institutions. Expanded measures should better reflect and reward the important work of both disciplinary and interdisciplinary teams at all career stages, and help sustain and stimulate a collaborative culture within ecology.
Keywords: Interdisciplinary collaboration; Success measures